Paralysis of the cytotoxic granule machinery is a new cancer immune evasion mechanism mediated by chitinase 3-like-1. Issue 11 (25th November 2021) - Darwich, Abbass; Silvestri, Alessandra; Benmebarek, Mohamed-Reda; Mouriès, Juliette; Cadilha, Bruno; Melacarne, Alessia; Morelli, Lapo; Supino, Domenico; Taleb, Alexandre; Obeck, Hannah; Sustmann, Claudio; Losurdo, Agnese; et al.
Abstract : Background: Natural killer (NK) cells require a functional lytic granule machinery to mediate effective antitumor responses. Evading the lytic cargo deployed at the immune synapse (IS) could be a critical step for cancer progression through yet unidentified mechanisms. Methods: NK cell antibody-dependent cellular cytotoxicity (ADCC) is a major determinant of the clinical efficacy of some therapeutic antibodies including the anti-HER2 Trastuzumab. Thus, we screened sera of Trastuzumab-resistant HER2 +patients with breast cancer for molecules that could inhibit NK cell ADCC. We validated our findings in vitro using cytotoxicity assays and confocal imaging of the lytic granule machinery and in vivo using syngeneic and xenograft murine models. Results: We found that sera from Trastuzumab-refractory patients could inhibit healthy NK cell ADCC in vitro. These sera contained high levels of the inflammatory protein chitinase 3-like 1 (CHI3L1) compared with sera from responders and healthy controls. We demonstrate that recombinant CHI3L1 inhibits both ADCC and innate NK cell cytotoxicity. Mechanistically, CHI3L1 prevents the correct polarization of the microtubule-organizing center along with the lytic granules to the IS by hindering the receptor of advanced glycation end-products and its downstream JNK signaling. In vivo, CHI3L1 administration drastically impairs the control of NK cell-sensitive tumors, while CHI3L1 blockade synergizes with ADCC to cure mice with HER2 +xenografts. Conclusion: Our work highlights a new paradigm of tumor immune escape mediated by CHI3L1 which acts on the cytotoxic machinery and prevents granule polarization. Targeting CHI3L1 could mitigate immune escape and potentiate antibody and cell-based immunotherapies.